2014
DOI: 10.1007/s12070-014-0756-9
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Doppler Ultrasound Evaluation in Patients with Pulsatile Tinnitus

Abstract: A wide range of conditions, including atherosclerosis, may lead to pulsatile tinnitus. The objective of this study was to evaluate the patients with pulsatile tinnitus by means of carotid Doppler ultrasound parameters. Thirty-four patients with pulsatile tinnitus were enrolled in the study. Internal carotid artery intima-media thickness (IMT), blood flow velocities and arterial lumen diameters (LD) were measured and compared with the control group. Mean end diastolic velocity (EDV) (32.29 ± 17.22) and IMT (1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…A similar view is presented by Melliere, Le Chevillier, Ecollan, and Fitoussi (1992) and Terzi et al (2015) Eckstein et al (2008) and Melliere et al (1992), showing that patients with the impaired blood flow in the cranial arteries also demonstrated postural disorders. Findings obtained by numerous authors and our research indicate that patients with this type of abnormalities should be examined for cerebral blood flow and inner ear disorders.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…A similar view is presented by Melliere, Le Chevillier, Ecollan, and Fitoussi (1992) and Terzi et al (2015) Eckstein et al (2008) and Melliere et al (1992), showing that patients with the impaired blood flow in the cranial arteries also demonstrated postural disorders. Findings obtained by numerous authors and our research indicate that patients with this type of abnormalities should be examined for cerebral blood flow and inner ear disorders.…”
Section: Discussionsupporting
confidence: 74%
“…A similar view is presented by Melliere, Le Chevillier, Ecollan, and Fitoussi (1992) and Terzi et al. (2015) who described otoneurological disorders in patients with cerebral ischemia caused by cranial artery stenosis. Kaźmierski, Kasielska, Bogusiak, Łysakowski, and Stelągowski (2012) found that up to 90% of patients with internal carotid artery stenosis felt vertigo, while tinnitus was experienced by about 80% of patients.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Carotid artery stenosis may be asymptomatic or have common neurological symptoms, such as motor and sensory disorders as well as vision or speech disturbances [2]. However, we usually encounter very discrete, non-specific symptoms of ischemia such as headaches, dizziness, tinnitus and hearing loss [3].…”
Section: Introductionmentioning
confidence: 99%